2019
DOI: 10.1021/acs.est.9b04956
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Effect of Sulfidation and Ferrous Dosing on Selenate Removal by Zerovalent Iron Under Aerobic Conditions

Abstract: Both the reactivity and the removal capacity of zerovalent iron (ZVI) for the target contaminant are important for applying ZVI in wastewater treatment. In this study, the feasibility of combining sulfidation treatment and Fe2+ dosing (S-ZVI/Fe2+) to enhance the performance of ZVI for Se­(VI) removal was comprehensively investigated under aerobic conditions. Se­(VI) was first adsorbed on the surface of ZVI particles and then reduced to Se­(IV) and Se(0) with Se(0) being the final product in S-ZVI/Fe2+ system. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 58 publications
0
26
0
Order By: Relevance
“…This suggested that the coexisting ions may influence the EE by affecting Se(VI) adsorption and the subsequent electron transfer from the Fe 0 core to Se(VI) at the water-particle interface. Given these facts, Fan et al (2019b) further confirmed that sulfidation coupled with Fe (II) dosing could synergistically improve the reactivity and selectivity of ZVI toward Se(VI) under aerobic conditions (Figure 5…”
Section: Coupled Effects Of Sulfidation and Ferrous Dosing On Se(vi) Removal By Zvimentioning
confidence: 55%
See 1 more Smart Citation
“…This suggested that the coexisting ions may influence the EE by affecting Se(VI) adsorption and the subsequent electron transfer from the Fe 0 core to Se(VI) at the water-particle interface. Given these facts, Fan et al (2019b) further confirmed that sulfidation coupled with Fe (II) dosing could synergistically improve the reactivity and selectivity of ZVI toward Se(VI) under aerobic conditions (Figure 5…”
Section: Coupled Effects Of Sulfidation and Ferrous Dosing On Se(vi) Removal By Zvimentioning
confidence: 55%
“…Therefore, future research should focus on illustrating the performance of the ZVI/Fe 2+ system toward Se(VI) on a pilot-scale (Fan et al, 2019a). Moreover, the feasibility of employing Fe 2+ to enhance the performance of ZVI should be examined with ZVI of different origins, different target contaminants, and in the presence of different background matrices (Fan et al, 2019a), as well as coupled with WMF or sulfidation (Fan et al, 2019b).…”
Section: Discussionmentioning
confidence: 99%
“…EE describes the fraction of electrons transmitted to the target contaminant over the amounts of electrons provided by ZVI and had been used to assess the selectivity of ZVI for reductive removal of the target contaminant (Fan, Sun, et al, 2019; Xu, Avellan, et al, 2020). Specific removal capacity (SRC) is defined as the ratio of the amount of removed metal(loid)s to the consumed Fe 0 , and it can be used to indicate the capacity of consumed Fe 0 to remove contaminants, regardless of the removal mechanism (Fan, Li, et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon could be highly related to the surface properties of ZVI altered by the metal(loid)s in solution. For example, the surface of ZVI could be passivated by Se(VI) at elevated concentration (Fan, Li, et al, 2019; Fan, Sun, et al, 2019; Liang et al, 2015), which decelerated both the consumption of DO and the removal of contaminants by ZVI. It was found that both the consumption rate of DO and the removal rate of the certain metal(loid) under open condition were larger than those under closed condition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation